The Dynamics of Hadith Studies in Southeast Asia: Study of Tanqîḥul Qawl by Imam Nawawi and Jawhar al-Mawḥȗb by Syekh Wan Ali - Vina Manzila Rofiah; Ubaidillah Ubaidillah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The study of Sharh Hadith develops along with the increasingly complex problems of society, especially related to the distortion of the hadith meaning. This research method uses a comparative method by analyzing literature data in the form of hadith sharh works of the two figures with supporting data sourced from primary and secondary books in the form of journals and manuscripts. Through Fazlur Rahman's book study and Hermeneutics-History approach, this study aims to explain how the model of hadith sharh and its contribution to the dynamics of hadith studies on the one hand and the writing of hadith sharh books in Southeast Asia. The results of the study: Kitab Tanqîḥul Qawl is superior in linguistics, narration, and quality of hadith, while Kitab Jawhar al-Mawḥȗb superior in substance aspects with richer courses. Then, the characteristics of the book of Tanqîḥul Qawl are patterned fiqh Imam Shafi'i because it is related to heterogeneous community traditions, so fiqh is not only interpreted as a religious command but also builds the brotherhood relations of the local community, while the book of Jawhar al-Mawḥub is in the style of Sufism of Imam Ghazali because the focus of Syekh Wan Ali's goal is the salvation of the world and the hereafter, it is explained in detail involving other scientific studies. Finally, the Book of Tanqîḥul Qawl and Jawhar al-Mawḥȗb contributed to providing reforms in the study of sharh related to social problems such as moral reconstruction, influencing the legal basis of marriage in Indonesia, and fostering moderate understanding to prevent religious fanaticism